UNSUR-UNSUR BAHASA JAWA KUNA PADA MASYARAKAT SUKU TENGGER - Jayendra Eka Putri, Dyah Selvia (Humanis; Volume 5. No. 2. November 2013, 2014)
The language is closely connected with the community. The language is growing due to the public as his supporters. Therefore, the position and the function of language in society. Functions of the language for communication in General, but a detailed language serves as a function of culture, community, private and education. As with any old Javanese which has its own rank and functions in the tenggerese community residing in the neighborhood of Mount Bromo, East Java. According to interviews, the tenggerese people still using the old Javanese in conversation even though not all old Javanese word they use. However, elements of the old Javanese still lumpy. Old Javanese elements found in the form of the words included in the word class of verbs, nouns, adjectives, adverbialen, numeralia, particles and conjunctions.
Keywords: Language Functions, language Elements, a small Community